Class actions in privacy law - Cofone, Ignacio N., 1987- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Class actions in privacy law are rapidly growing as a legal vehicle for citizens around the world to hold corporations liable for privacy breaches. Current and future developments in these privacy class actions therefore stand to shift the corporate liability landscape for companies that interact with people's personal information. Privacy class actions are at the intersection of civil litigation and data protection. The outcomes of ongoing and future litigation are integral to the evolution of privacy law and data protection law across jurisdictions. Moreover, developments in privacy class actions are raising numerous issues of substantive law as well as challenges to the established procedures governing class action litigation. This book brings together established scholars in privacy law, data protection law, and collective litigation to offer a detailed perspective on the present and future of collective litigation for privacy claims. Taking a comparative approach, this book incorporates considerations from consumer protection law, procedural law, cross-border litigation, tort law, and data protection law, which are key to understanding the development of privacy class actions. In doing so, it offers an analysis of the novel challenges they pose for courts, regulatory agencies, and litigators, together with their potential solutions"--
"Routledge Focus" -- Cover.
OCLC-licensed vendor bibliographic record.
Keywords: Class actions (Civil procedure); Privacy, Right of; Tort liability of corporations; Data protection -- Law and legislation; LAW / General